(untitled) (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the aetiology of total knee arthroplasty (TKA) failure and assess the functional outcome of patients who underwent revision total knee arthroplasty. Methods: It was a descriptive study conducted in Orthopaedic department Aga khan university hospital Karachi from 3rd Jan 2010 to 25th December 2020. All patients with primary total knee replacement who underwent revision total knee arthroplasty were included in this study. The indications for revision arthroplasty were documented. Functional outcome of revision total knee arthroplasty was assessed at 6 months with Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) questionnaire. The preoperative and post operative WOMAC score were compared with Student-t test an P value calculated. P value <0.05 was considered significant Results: The total number of patients included in this study were 29 with 33 knees. The mean age was 60.60 ±6.78 years. Majority(86.20%,n=25) of our patients were female while males were only 4(13.7%).Unilateral revision arthroplasty was done in 25(86.20%) patients and bilateral in 4(13.79%). The aetiology of revision arthroplasty was Infection in 15(45.45%) knees, aseptic loosening in 14(42.42%) and periprosthetic fractures in 4 knees (12.12%). The pre revision WOMAC pain score was 18.4±3, stiffness score 8.1±7 and function score was 72.5±4.Revision arthroplasty yielded significant improvement in WOMAC score at 6 months with WOMAC pain score of 2.2±1,stiffness 3.4±6 and function 10.4±4(P<0.05). Conclusion: Infection was the most common cause of revision arthroplasty in our series. Revision arthroplasty yielded acceptable functional outcome in majority of our patients.